Altering patterns of sensorimotor network in patients with different pathological diagnoses and glioma‐related epilepsy under the latest glioma classification of the central nervous system. (5th February 2023) - Fang, Shengyu; Li, Lianwang; Weng, Shimeng; Guo, Yuhao; Fan, Xing; Jiang, Tao; Wang, Yinyan
Abstract: Aims: We aimed to clarify the relationship between alterations in functional networks and glioma‐related epilepsy (GRE) in patients with different molecular diagnoses. Methods: We enrolled 160 patients with prefrontal gliomas and different histories of GRE. The patients were grouped based on the latest pathological glioma classification and GRE history. Graph theory analysis was applied to reveal alterations in the sensorimotor networks among various subgroups. Binary logistic regression was used to identify risk factors for preoperative GRE onset. Results: Decreasing shortest path length was found in patients with GRE, regardless of the chromosome 1p/19q status. Nodes located in the premotor and supplementary motor areas showed decreased nodal betweenness centrality and vulnerability in patients with GRE and chromosome 1p/19q intact. Additionally, the node on the primary motor area showed decreased nodal vulnerability but the node on the sensory‐related thalamus increased in patients with GRE and chromosome 1p/19q co‐deletion. Decreased shortest path length, grade 2, and decreased nodal betweenness centrality of the premotor area were risk factors for GRE. Conclusion: Decreased shortest path length was a characteristic alteration in GRE and prefrontal glioma. Alterations in global properties were similar, but nodal properties were different in patients with GRE and different chromosome 1p/19q statuses. Abstract : Glioma with different molecular classification would cause different network alterations that induce preoperative glioma‐related epilepsy. Oligodendroglioma recruited distant cortices but astrocytoma only recruited adjacent cortices to reorganize sensorimotor network when the glioma grew on the prefrontal lobe. In this figure, the green and blue nodes were located on the Brodmann area 6 that altered nodal properties in patients with astrocytoma, whereas the red and yellow nodes were located on the Brodmann area 4 and sensory related thalamus that altered nodal properties in patients with oligodendroglioma. BA, Brodmann area. Nodes No. 1 and No. 5: A6cdl, caudal dorsolateral BA 6; Nodes No. 2 and No. 6: A6m, medial BA 6; Nodes No. 3 and No. 7: A4ul, upper limb region of BA 4; Nodes No. 4 and No. 8: Stha, sensory thalamus.